2014
DOI: 10.3389/fnins.2014.00276
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and structural brain development

Abstract: Recent advances in neuroimaging methods have made accessible new ways of disentangling the complex interplay between genetic and environmental factors that influence structural brain development. In recent years, research investigating associations between socioeconomic status (SES) and brain development have found significant links between SES and changes in brain structure, especially in areas related to memory, executive control, and emotion. This review focuses on studies examining links between structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
303
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(334 citation statements)
references
References 66 publications
18
303
1
12
Order By: Relevance
“…Our study contributes to a growing literature on the role played by brain structure and physiology in explaining associations between environmental factors and cognition among youth [3,46]. If disadvantage and adversity have unique implications for neurocognitive development, as our results suggest, then remediation is likely to be more effective at improving educational outcomes when targeted to specific peer-reviewed) is the author/funder.…”
Section: Discussionsupporting
confidence: 48%
“…Our study contributes to a growing literature on the role played by brain structure and physiology in explaining associations between environmental factors and cognition among youth [3,46]. If disadvantage and adversity have unique implications for neurocognitive development, as our results suggest, then remediation is likely to be more effective at improving educational outcomes when targeted to specific peer-reviewed) is the author/funder.…”
Section: Discussionsupporting
confidence: 48%
“…However, currently there is not enough data from other cultures to begin to grasp the effects of such variation, and the field will benefit significantly from more crosscultural comparisons [70]. Note also that so-called 'SES effects' are not solely reducible to cultural influences; they are also linked to a host of environmental factors (e.g., diet [71] and activity [72]) that affect brain development [73].…”
Section: Relationships Between Language and The Environmentmentioning
confidence: 99%
“…Previous publications with this longitudinal data reported that socioeconomic conditions and maternal mental health were associated with language (Piccolo et al, 2012), memory and executive function performance, and stress (Piccolo et al 2016). Studies have reported that environmental-such as socioeconomic status, home language environment, parental style, parental mental health-and biological factors-cortisol and neurotransmitter levels, for example-may influence the typical sequence of child development, affecting cognitive abilities (Brito & Noble, 2014;Johnson et al 2016;Noble et al, 2015). The stimulation of sensorimotor abilities in the first years of life seems to be crucial for the development of subsequent cognitive skills (Hernandez & Caçola, 2015;Tierney & Nelson, 2009).…”
Section: Discussionmentioning
confidence: 61%